Reconstruction of spiritual marketing, culture of innovation, quality of work life, and retainers for tourism industry SMEs in East Java - Adya Hermawati; Choirul Anam; Suwarta Suwarta; Endah Puspitosarie (Administrative Sciences, 2022)
The purpose of this study is to reconstruct and develop a more comprehensive competitive advantage concept model by combining the variables of spiritual marketing, innovation culture, quality of work life, and rewards for the tourism industry's Small and Medium-Sized Enterprises (SMEs) in East Java. This research uses a positive (quantitative) approach. A quantitative approach involves a survey method applied to a sample taken from the population. Data analysis was performed using the statistic method known as IPA (importance performance analysis). The analysis unit encompasses the employees of tourism industry SMEs in East Java Province. Among all the variables in this study, the biggest analysis gap is innovative culture. Tourism industry SMEs in East Java Province should prioritize innovative culture to help improve the performance of SMEs. The smallest analysis gap in this study is spiritual marketing. Tourism industry SMEs must at least maintain their performance. The scientific contribution of this study is its research object, which is tourism industry SMEs in East Java Province. Another scientific contribution is that this study attempts to reconstruct or develop a more comprehensive model of competitive advantage by including spiritual marketing and quality of work life as explanatory variables.
Keywords: 350; innovative culture; quality of work life; retainers; spiritual marketing